NILAI EKONOMI TEMBAWANG AMPAR DI DESA CEMPEDAK KECAMATAN TAYAN HILIRKABUPATEN SANGGAU - budin, Ra; Roslinda, Emi; Kartikawati, Siti Masitoh (JURNAL HUTAN LESTARI, 2015)
Land use system of the local community at West Kalimantan with anunique ecosystem is tembawang. In the TembawangAmpar, durian (DuriozibertinusMurr) is the dominan trees that must be contained therein. During the utilization of the results of TembawangAmpar economically tend to be dominated from the fruits. The economic value is very small compared with the products and services that are actually produced TembawangAmpar. This study aimed to count the economic value of TembawangAmpar through its direct use value. The research was conducted in May 2015. The respondents consisted of 70 heads of families determined by census. Data was obtained and collected through direct observation in the field, and interviews. To calculate the economic value the market price method was used. The study points out that the direct value of TembawangAmparis Rp 239.852.402,-/year, or equivalent to Rp 33.545.791,-/ha/, consisting of the use of timber (logs), firewood, fruits, slick, latex rubber, bamboo, medicinal plants, and animals. These results indicate that TembawangAmpar should have produced not only fruit alone, but also other economic values. Keywords: Direct Use Value, Economic Value, TembawangAmpar.